2006
DOI: 10.2165/00002018-200629090-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Drug Interaction Profiles of Proton Pump Inhibitors

Abstract: Proton pump inhibitors are used extensively for the treatment of gastric acid-related disorders because they produce a greater degree and longer duration of gastric acid suppression and, thus, better healing rates, than histamine H(2) receptor antagonists. The need for long-term treatment of these disorders raises the potential for clinically significant drug interactions in patients receiving proton pump inhibitors and other medications. Therefore, it is important to understand the mechanisms for drug interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
3
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(210 citation statements)
references
References 98 publications
4
182
3
19
Order By: Relevance
“…Proton pump inhibitors (PPIs) are highly effective in the treatment and symptomatic relief of peptic ulcers, by inhibiting H + ,K + -adenosine triphosphate (ATP)ase in the gastric parietal cells (16). The effects of pantoprazole (PPZ), one type of PPI, on PKM2 were hypothesized to be associated with the inhibitory efficacy of PPZ (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are highly effective in the treatment and symptomatic relief of peptic ulcers, by inhibiting H + ,K + -adenosine triphosphate (ATP)ase in the gastric parietal cells (16). The effects of pantoprazole (PPZ), one type of PPI, on PKM2 were hypothesized to be associated with the inhibitory efficacy of PPZ (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, treatment with cyclosporine at a trough level of at least 150 ng/mL is necessary for maintaining remission [23]. In our case, the patient was taking omeprazole at the start of cyclosporine, and it is reported that omeprazole reduces the hepatic clearance of cyclosporine by inhibition of cytochrome P450 enzyme system, thus leading to higher cyclosporine levels with the same dosage [24]. Furthermore, the clearance rate of cyclosporine has shown to be diminished under uremic condition [25].…”
Section: Discussionmentioning
confidence: 69%
“…The results of some clinical studies show that the best alternative for omeprazole, which is the moderate CYP2C19 inhibitor, is pantoprazole which seems to have much lower potential to inhibit CYP2C19. 12 In the current study, pantoprazole was recommended more often in comparison to other PPIs available, while some patients had not received omeprazole therapy yet.…”
Section: Clopidogrel and Omeprazole Co-medicationmentioning
confidence: 77%